ELECTRIC TRANSMISSION OF THE HYBRID ELECTRIC VEHICLES - Gheorghe GÎLCĂ (Fiabilitate şi Durabilitate)
The paper presents the main components of an electric or hybrid car. This means that it is desired to characterize the technologies and models used most in the implementation of vehicle components: accumulator batteries, generator, electric motor and gearbox.